Experts’ consensus to identify elements of career management competencies in Work-Based Learning (WBL) program using fuzzy delphi analysis - Marwan, Hazlina; Ali, Azita (Kassel University Press, 2019)
This study aimed to obtain experts‘ opinion and consensus on the elements of career management competencies that can be developed through the Work-Based Learning (WBL) program in polytechnic.